Nanoporous reduced graphene oxide and polymer composites as efficient counter electrodes in dye-sensitized solar cells - Sudhakar, Vediappan; Singh, Anup Kumar; Chini, Mrinmoy Kumar (ACS Applied Electronic Materials, 2020)
The introduction of an efficient and precious platinum (Pt) free counter electrode (CE) for dye-sensitized solar cells (DSSCs) is an important aspect to address. In this report, we have employed nanoporous reduced graphene oxide (PG) containing PEDOT:PSS-PG composite on FTO substrate as CEs, which have shown excellent diffusion of I-3(-), remarkable photocatalytic activity, and better device performance along with desired stability. The investigated cathode material has been prepared by mixing PGs and highly conducting PEDOT:PSS. Experimental measurements and analyses such as electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and so on indicate that PEDOT:PSS-PG is a promising cathode material for a Pt-free CE in DSSCs. EIS indicates that the PEDOT:PSS-PGs have lower interfacial charge-transfer resistance because of their high electrical conductivity and superior electrocatalytic activity. The achieved photoconversion efficiency (eta) of a DSSC employing the Pt-free PEDOT:PSS-PG/FTO CE is 9.57%, which is found to be comparable to that of Pt/FTO CE based DSSC (9.64%) under a simulated solar light illumination of 100 mW/cm(2).
Keywords: counter electrode; Dye-sensitized solar cells; electrocatalytic activity; PEDOT:PSS; Reduced graphene oxide